Ayurvedic Management of Hepatocellular Jaundice - A Case Report - Rakesh Moolya; Bargale Sushant Sukumar (RGUHS Journal of AYUSH Sciences)
Jaundice is a disorder characterized by yellowish pigmentation of the skin sclerae mucous membrane and excretions due to hyperbilirubinemia and bile pigment deposition. There is a disruption in the balance between bilirubin production and clearance. There are three different forms of jaundice hemolytic hepatocellular and obstructive. Jaundice is referred to as lsquoKamala rogarsquo in Ayurveda. Excessive intake of Ushna hot Tikshna or Pitta Prakopaka aggravating diet is the primary cause of Kamala. This results in increased pitta dosha along with the vitiation of the Mamsa muscles and Rakta blood Dhatus. The present case report discusses the details of a 28-year-old female patient who complained of Peeta yellowish discoloration of her eyes nails and urine as well as a decreased appetite fever increased liver function test values SGPT- 525 UL and SGOT- 719 UL and a total bilirubin content of 15.2 mgdL. Based on the physical examination and liver functional test results a diagnosis of Kosthashritha Kamala was made. This condition bears a striking resemblance to hepatocellular jaundice. According to Ayurveda Virechaka a purgative Rasayana a rejuvenator and Dhatuvardhaka which nourishes bodily tissues are the next steps in the treatment of Kamala Roga after Virechana. Herbomineral formulations such as Agnitundi Vati Nirocil Bhumyalaki capsule Patolokaturohindyadi Kashaya and Avipattikara Choorna should be administered internally for 30 days together with Pathya Palana. In the case presented all the parameters including the liver function test showed improvement SGOT - 39.3 UL SGPT-21 UL and total bilirubin 1.8 mgdL.